EL PAPEL DE LA EDUCACIÓN FÍSICA PARA COMBATIR LA DISCRIMINACIÓN RACIAL EN LA ESCUELA CON LA ASOCIACIÓN DEL PSICÓLOGO - Mourão, Nádia Raquel Dutra de Morais (2020)
The main theme of this article is the role of Physical Education as one of the possible instruments to be used in tackling racial discrimination in the school environment. For this, we conducted a bibliographic research and through such readings and research, we found ways to reinforce our theme, as well as identifying aspects that provide a reflection on the discriminatory process, its possible psychological consequences and some strategies to minimize it. As an illustration, we present an example that occurred in the municipality in which we operate, describing the trajectory of a black elementary school student who became a professional athlete. Our objective was to demonstrate that the practice of sport, through Physical Education and psychological assistance, presents itself as possible ways to be used by the school and by society to discuss discrimination in the school environment, which can also be a form of valorization discriminated student. The results of the research point out that Physical Education and the psychologist's partnership can be valuable instruments in the fight against racial discrimination, when directed to actions that generate reflections and taking anti-racist attitudes.